Wound Healing Activity of Arum Maculatum - Ayse ARZU SAKUL; Mehmet Evren OKUR; Sule AYLA; Benay DAYLAN; Ayse Esra KARADAG; Sebnem BATUR; Ekrem Musa OZDEMIR; Ebrar ALTINALAN; Mehmet Yalcin GUNAL (Medeniyet Medical Journal)
Objective: In this study, the antioxidant properties of Arum maculatum plant were evaluated. This study reported for the first time the wound healing activity of the methanol extract of A. maculatum fruits. This study aimed to assess and determine the possible pharmacological activities of A. maculatum and evaluate its potential to act as a wound care plant. Methods: The antioxidant and antimicrobial activities of A. maculatum were investigated using excisional in vivo and in vitro wound healing mouse models. A total of 32 Balb-c mice were used, which were equally, divided into four groups: saline control group, control group, A. maculatum group, and Centella asiatica extract group. Treatment applications were performed topically once per day. Wound area narrowing, wound healing percentage, and epithelialization time were analyzed. Results: A. maculatum application supported the healing process in in vivo and in vitro wound models. A. maculatum contributed to the healing process by promoting granulation tissue formation, epidermal regeneration, and angiogenesis. Conclusions: Wound healing is a complex and well-organized process that requires communication between cells. The antioxidant and antimicrobial activities of A. maculatum extract have been determined by current studies. A. maculatum extract may provide significant benefits in promoting the wound healing process.